2020
DOI: 10.1155/2020/5369025
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Mechanism of Wuwei Qingzhuo San against Hyperlipidemia Based on TCM Network Pharmacology and Validation Experiments in Hyperlipidemia Hamster

Abstract: Wuwei Qingzuo San (WWQZS), as a renowned traditional Mongolian patent medicine approved by Chinese State Food and Drug Administration, is used to treat hyperlipidemia, indigestion, and other ailments related to disorder of production of essence and phlegm, a typical abnormal metabolism of blood in traditional Mongolian medicine. A combination of network pharmacology and validation experiments in hyperlipidemia hamster is used to understand the potential mechanism of WWQZS for hypolipidemic effects, further for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…By comparing with the negative control, significant differences were observed in these two groups (p < 0.05). These data suggested that Coptidis rhizoma had good hypoglycemic effect, which was in agreement with previous reports [141,5].…”
Section: Blood Glucose Levels Of Ratssupporting
confidence: 94%
See 1 more Smart Citation
“…By comparing with the negative control, significant differences were observed in these two groups (p < 0.05). These data suggested that Coptidis rhizoma had good hypoglycemic effect, which was in agreement with previous reports [141,5].…”
Section: Blood Glucose Levels Of Ratssupporting
confidence: 94%
“…As a shade-loving plant, Coptidis usually grows in cool and damp valleys or shaded in dense forests at altitudes of 1000 -1900 meters. Clinically, it has been widely used to treat gastroenteritis, dysentery, diabetes mellitus, and severe skin diseases [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In China and many East Asian countries, traditional Chinese medicine (TCM) is extensively adopted for the prophylaxis and treatment of hyperlipidemia in clinical practice [ 7 ]. Indeed, TCM is thought to present several unique advantages for prevention or treatment of hyperlipidemia, due to its action through multiple components, approaches, and targets [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the five herbs of WQS contain tannins, alkaloids, flavonoids, organic acids, and other components ( Kumar et al, 2011 ; Ge et al, 2021 ) which have good effects in anti-inflammatory, immunomodulatory, and metabolic regulation. Our previous studies found that WQS has an attractive hypolipidemic and hepatoprotective effect in the hyperlipidemic hamster ( Li et al, 2020 ), and associated endogenous metabolites in biological fluids were analyzed qualitatively and quantitatively using metabolomics ( Hu and Xu, 2014 ). But its mechanism of regulation of cholesterol metabolism remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, it was predicted that WQS increases cholesterol catabolism through the upregulation of CYP7A1 and inhibits hepatic HMGCR expression through the upregulation of p-AMPK, thereby inhibiting cholesterol synthesis and lowering blood lipids( Li et al, 2020 ). Therefore, we extended our previous study to detect endogenous metabolites in mouse serum by UPLC-QTOF/MS-based serum metabolomics to determine whether the lipid-lowering mechanism of WQS is related to endogenous substances.…”
Section: Introductionmentioning
confidence: 99%